2018
DOI: 10.5812/jhealthscope.63866
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Trend of Health System Responsiveness in Iran Using Household Survey (Before and After the Implementation of Health Transformation Plan)

Abstract: Background: One of the 3 main goals of any health system is to meet the non-medical expectations of individuals while interacting with health system. The purpose of this study is to evaluate the health system responsiveness before and after the implementation of the health transformation plan (HTP) in Iran. Methods: In this longitudinal study, a household survey was conducted at the district 17 of Tehran, Iran in 2003, 2008. A sample of 600 families was selected using a two-stage cluster sampling approach. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 18 publications
9
14
2
Order By: Relevance
“…Some evidences from low and middle income countries shows that health system responsiveness in health care delivery tends to be ignored and many times not sufficient to meet patient's non-medical demands [10]. Currently, there is a growing interest in evaluating people's experience with health care services in Low and Middle-income countries so as to ascertain the level of satisfaction of patients to healthcare system [11][12][13][14][15]. In all settings, the individuals who are always and usually touched by poor responding health care system are women, as their demands for the health care system are wide and are multi-dimensional [16].…”
Section: Introductionmentioning
confidence: 99%
“…Some evidences from low and middle income countries shows that health system responsiveness in health care delivery tends to be ignored and many times not sufficient to meet patient's non-medical demands [10]. Currently, there is a growing interest in evaluating people's experience with health care services in Low and Middle-income countries so as to ascertain the level of satisfaction of patients to healthcare system [11][12][13][14][15]. In all settings, the individuals who are always and usually touched by poor responding health care system are women, as their demands for the health care system are wide and are multi-dimensional [16].…”
Section: Introductionmentioning
confidence: 99%
“…As they are developed from an extensive array of disciplines, responsiveness domains analyse the function of the health care system from the way patients experience care, the treatment procedures and the environment around the services [16][17][18]. Although responsiveness has increasingly been promoted as a key goal of any health system, its measurement remains scarce [11,12,17,19,20]. Studies on responsiveness have been more common in high-income countries [14,[21][22][23] than in LMICs [17,24].…”
Section: Introductionmentioning
confidence: 99%
“…In the former, health care users have mainly reported concerns regarding trust, long waiting times, lack of empathy and friendliness, and limited involvement in decisionmaking [22,23,25]. In the case of the LMICs, different studies [9,13,15,20] have shown choice of service provider, autonomy, prompt attention, quality of basic amenities and confidentiality as important areas of concern in terms of responsiveness. In sub-Saharan Africa, studies from Nigeria [11] and South Africa [26] have also shown the usefulness of the responsiveness domains in examining the operationalisation of health systems in the context of health insurance schemes.…”
Section: Introductionmentioning
confidence: 99%
“…As they are developed from an extensive array of disciplines, responsiveness domains analyse the function of the health care system from the way patients experience care, the treatment procedures and the environment around the services (16)(17)(18). Although responsiveness has increasingly been promoted as a key goal of any health system, its measurement remains scarce (11,12,17,19,20). Studies on responsiveness have been more common in high-income countries (14,21-23) than in LMICs (17,24).…”
Section: Introductionmentioning
confidence: 99%
“…In the former, health care users have mainly reported concerns regarding trust, long waiting times, lack of empathy and friendliness, and limited involvement in decision-making (22,23,25). In the case of the LMICs, different studies (9,13,15,20) have shown choice of service provider, autonomy, prompt attention, quality of basic amenities and con dentiality as important areas of concern in terms of responsiveness. In sub-Saharan Africa, studies from Nigeria (11) and South Africa (26) have also shown the usefulness of the responsiveness domains in examining the operationalisation of health systems in the context of health insurance schemes.…”
Section: Introductionmentioning
confidence: 99%